Analysis of the Causes of Ship Stress Due to Incorrect Cargo Placement on the MV. Kanal Mas - Defnico Eka Arvenda Garfiosa; Anak Agung Ngurah Ade Dwi Putra Yuda; Jaka Septian Kustanto; Fazri Hermanto (International Journal of Science and Environment (IJSE), 2026)
This research is motivated by the increasing risk of ship stress on container ships due to imbalanced cargo distribution that can trigger hogging and sagging conditions. The purpose of this study is to analyze the causes of ship stress due to incorrect cargo placement on board the MV. Kanal Mas and to identify efforts to optimize cargo distribution. This study uses a descriptive qualitative approach. The study population includes all officers and crew, with samples selected using purposive sampling consisting of the Captain, First Officer, Second Officer, Third Officer, and related crew. The research instrument is the researcher himself with data collection techniques through observation, interviews, and documentation. Data analysis uses the interactive model of Miles, Huberman, and Saldaña which includes data reduction, data presentation, and conclusion drawing. The results of the study indicate that ship stress is mainly caused by port operational limitations, out-of-sequence conditions, and uneven cargo distribution. The conclusion of the study shows that ship stress on the MV. Kanal Mas is more influenced by operational factors than technical errors in the preparation of the bay plan, so that it is necessary to strengthen coordination and continuous supervision of cargo distribution